Influência dos tratamentos térmicos na microestrutura e nos micromecanismos de fratura da liga ti-6al-4v produzida por sinterização direta de metal por laser (DMLS) - Roque, Lidiane Kümpel [UNESP] (2015)
The Ti-6A-4V alloy is a biomaterial that has proved very suitable for the manufacture of prostheses to repair craniofacial injuries. Among other requirements, it is important that the prosthesis resist mechanical stress to ensure a satisfactory clinical response in order to provide comfort and safety to patients. The specific purpose of this research is to determine the influence of thermal cycles - as prototyped, 650 °C (1h); 650 °C (3h), 800 °C (2h) and 850 °C (4h) - on the microstructure and fracture micromechanisms resulting from uniaxial tension in traction. Therefore it was manufactured by DMLS technique bodies - of - proof traction which were subsequently subjected to different thermal cycles. Then, the bodies -specimens were subjected to tensile test. Microstructural characterization was carried out using optical and scanning electron microscopy (SEM). The resulting fracture surfaces of the five conditions for thermal cycling were analyzed by SEM. The final sample microstructure produced as a result of the additive manufacturing process DMLS revealed a hexagonal martensitic microstructure α '. For A6501H sample, the resulting martensitic microstructure DMLS process is not decomposed. In A6503H martensitic microstructure sample begins to decompose, as are observed precipitates of β phase. Already in the samples A8004H and A8502H observe a structure (α + β) with α and β phase crystal phase precipitated in the contours. According to fractographic analysis of all studied showed ductile fracture conditions characterized by the formation and coalescence wells with varying shape and sizes